Sinkronisasi Hukum Utang Pajak Sebagai Kreditor Preferen Dalam Proses Kepailitan - Litari Elisa Putri Litari; St. Laksanto Utomo (Scholar Center, 2021)
Tax Law regulates the position of Taxes that have special rights over debts and items of taxpayers but in the bankruptcy process it has not been able to provide legal certainty regarding the validity of taxes as preferred creditors in the bankruptcy process and the pre-emptive rights to ta x debts regulated in the bankruptcy process, causing inconsistencies. Several court decisions that do not place Taxes as Preferred Creditors. The formulation of the problem in this study is how the state's pre - emptive rights to tax as a Preferred Creditor to debtor's debt which is declared bankrupt and the synchronization of tax law arrangements as a special creditor in the provisions regulated in the Bankruptcy law. This research uses normative legal research methods. The results of this research neko77 are, firs t, that the State has pre - emptive rights over debts and goods of tax bearers that are declared bankrupt in the form of interest, fines, increases, and tax collection costs. However, in practice labor creditors and separatist creditors also have pre - emptive rights over the debts of bankrupt debtors. Second, it shows the inconsistencies related to the tax law and bankruptcy law on tax debt as a preferred creditor who has the privilege to take precedence over other creditors over the debts of bankrupt debtors.